2020
DOI: 10.21873/cgp.20221
|View full text |Cite
|
Sign up to set email alerts
|

Micro RNAs Promoting Growth and Metastasis in Preclinical In Vivo Models of Subcutaneous Melanoma

Abstract: During the last years a considerable therapeutic progress in melanoma patients with the RAF V600E mutation via RAF/MEK pathway inhibition and immunotherapeutic modalities has been witnessed. However, the majority of patients relapse after therapy. Therefore, a deeper understanding of the pathways driving oncogenicity and metastasis of melanoma is of paramount importance. In this review, we summarize microRNAs modulating tumor growth, metastasis, or both, in preclinical melanoma-related in vivo models and possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 172 publications
(269 reference statements)
0
2
0
Order By: Relevance
“…MicroRNAs (miRNAs/miRs) are small noncoding RNAs that regulate target genes by recognizing a complementary mRNA sequence and subsequently repressing its translation [ 8 ]. A growing number of studies have uncovered the key regulatory role of miRNAs in cancer metastasis [ 9 11 ]. On the basis of miRNA assay, we found that miR-5100 expression is increased in melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are small noncoding RNAs that regulate target genes by recognizing a complementary mRNA sequence and subsequently repressing its translation [ 8 ]. A growing number of studies have uncovered the key regulatory role of miRNAs in cancer metastasis [ 9 11 ]. On the basis of miRNA assay, we found that miR-5100 expression is increased in melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma preferentially metastasizes through the lymphatic pathway, but can spread through the bloodstream in some cases. The main organs where melanoma metastases can develop are the lungs, brain, liver, and bones [5].…”
Section: Introductionmentioning
confidence: 99%